عبدالله الطيب شاعر التراث : مكانته الأدبية وظواهر لغوية فى ديوانه " بانات رامة " - حسين، نصر الدين إبراهيم أحمد; إدريس، موسى سعيد طه (الجامعة الإسلامية العالمية, 2018)
This study, by making use of the descriptive and analytical methods, aims to explore the literary position of the ‘Abdullah al-Ṭayyib as a traditional poet and his language characteristics in his anthology “Banāt Ramah”. His literary position is pointed out through his interest in the Arabic poetic tradition and his commitment to it in his poems as well as the language characteristics which distinguish him in his anthology. The study concludes among others: that the poems of ‘Abdullah al-Ṭayyib are abundantly infused with aesthetical features of language, among them is the use of different symbols; some represent the nation while others represent the barren deserts. He made use of the style of the earlier Arabic traditional poets both in words and senses. His inclination to the traditional elements is rare in the time when contemporary poets mostly would turn away from it. Hence, he made use of some of the traditional openings and some phrases in the ancient traditional poems, thus earning himself a special characteristic as found in the anthology.
يسعى الباحث من خلال اتباع المنهجين: الوصفي والتحليلي، إلى دراسة موضوع عبد الله الطيب شاعر التراث: مكانته الأدبية وظواهر لغوية في ديوانه (بانات رامة)؛ حيث يبرز البحث مكانة عبد الله الطيب الأدبية، مبينا اهتمامه بالتراث الشعري العربي والاقتداء به في أشعاره، كما يتناول الظواهر اللغوية التي تميز بها هذا الديوان، ويهدف هذا البحث إلى إظهار مكانة عبد الله الطيب الأدبية، وإبراز الظواهر اللغوية في ديوانه بانات رامة. توصلت الدراسة إلى أن شعر عبد الله الطيب يزخر بكثير من الظواهر اللغوية الفنية، ومنها استعمال الشاعر للرموز المختلفة؛ حيث يرمز بها للوطن؛ بينما رمز للغربة بالصحراء الجرداء، واستمد الطيب معجمه اللغوي في أشعاره مما كان يجري على ألسنة الشعراء العرب القدامى لفظا ومعنى، وأبرز البحث اقتراب عبد الله الطيب من النصوص الشعرية العربية القديمة في عصر ندر فيه اقتراب أحد من هذا الشعر، فكان استمداده لبعض مطالع، ومقاطع قصائده من الشعر العربي القديم، مميزا لإنتاجاته الشعرية الواردة في الديوان.
Keywords: الأدب العربى -- الشعر العربى -- الشعراء العرب -- التراث الشعرى -- الطيب، عبدالله